PERAN AUSTRALIA MELALUI ACIAR (Australian Centre For International Agricultural Research) DALAM BANTUAN PEMULIHAN SEKTOR PERTANIAN ACEH PASCA TSUNAMI TAHUN 2004 - Rina Susanti; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The reserach aims to determine how the role of foreign countries involves in humanitarian aid and perceptive disaster response to the disaster-affected country. The case of this research is about the Australian aid toward the tsunami-affected region in Indonesia which is Aceh province in 2004. One of Australia's roles in the tsunami disaster is the recovery assistance in the agricultural sector undertaken by ACIAR (Australian Centre For International Agricultural Research).This research uses qualitative methods with techniques of writing a literature review through the secondary data which are already available in the literature and website searches. The collected data are analyzed with theoretical approaches related to International Relations, International Cooperation and the Role of the State. The author also uses the concept of foreign aid in the case of this study.The result of this research indicates any form of cooperation between the Australian government and the Indonesian government, especially in Aceh on the recovery of the agricultural sector through ACIAR assistance. The formed cooperations in ACIAR projects cooperate with the Agency for Agricultural Technology (BPTP) Aceh. ACIAR assistance program is the rehabilitation of land and crop management to increase agricultural productivity. ACIAR project aid has given a positive impact on farmers' agricultural activities along the coastal areas of Aceh after the tsunami.Keywords: Disaster, Foreign Aid, ACIAR, Rehabilitation of land